Special education : a reference book for policy and curriculum development - Sacks, Arlene (Grey House Publishing, 2018)
A reference work that presents a chronology focusing on special education, its development, and the important issues that both positively and negatively affect the field. Updated through current events, this edition provides an excellent introduction to special education in all of its practical aspects-how it developed, its curriculum, assessment issues, the law, and advocacy--Provided by publisher.